Real‐world use of emicizumab in patients with haemophilia A: Bleeding outcomes and surgical procedures. Issue 4 (20th April 2020) - McCary, Isabella; Guelcher, Christine; Kuhn, Jan; Butler, Regina; Massey, Gita; Guerrera, Michael F.; Ballester, Lance; Raffini, Leslie
Abstract: Introduction: Emicizumab is a recombinant humanized bispecific antibody that bridges factor IXa and factor X to mimic the cofactor function of factor VIII. It is approved to prevent bleeding in patients with haemophilia A (HA). Outside of clinical trials, there is limited data on outcomes of patients treated with emicizumab, particularly in children without inhibitors. Aim: To report our experience treating patients with emicizumab, including (a) bleeding rates pre and postemicizumab, (b) peri‐procedural management and outcomes and (c) serious drug‐related adverse events. Methods: Multicentre observational study in patients with HA who started emicizumab prior to 15 May 2019. Data collection continued until 15 October 2019 and included demographics, disease history, bleeding events, invasive procedures, thrombotic events and death. Annualized bleeding rates (ABR) prior to emicizumab were compared to postemicizumab. Results: Ninety‐three patients (including three females) met inclusion criteria, 19 with an active inhibitor. Median age was 8.6 years; patients <12 years without inhibitors (n = 49) accounted for the majority. ABR dropped from 4.4 (inhibitors) and 1.6 (non‐inhibitors) to 0.4 (both groups) on emicizumab, P = .0012 and .0025, respectively. There were 28 minor (21 port removals) and two major procedures. Three patients received 1‐2 doses of unplanned factor postoperatively to treat minor bleeding events. No patient discontinued therapy, and there were no thrombotic events or deaths. Discussion: Our favourable clinical experience with emicizumab is similar to that reported in the clinical trials. Notably, this is the largest cohort of patients <12 years without inhibitors treated with emicizumab.